The morphology of the dorsal and ventral skin of Triturus karelinii (Caudata: Salamandridae) - BİNGÖL ÖZAKPINAR, ÖZLEM (DE GRUYTER OPEN LTD, 2011)
In this study, for the first time, the morphology of the dorsal and ventral skin of Triturus karelinii using light microscopy through histochemical methods was described. The skin exhibited basic morphological characteristics of the other urodeles: the epidermis composed of keratinized stratified epithelium with numerous conical protrusions and the dermis subdivided into spongy and compact layers. In the spongious dermis, three distinct types of glands were observed, namely serous, mucous and mixed glands. These glands were alveolar and occurred in both males and females. The morphologies of all three skin glands differed from anurans and other urodeles, having peculiar characteristics. Serous glands exhibited three different appearances. An unusual finding in mucous glands was the different appearance of their granules, showing diverse density after staining with PAS and AB. The histochemical analysis clearly demonstrated the presence of neutral, acid and sulfated mucins in the adenocytes of mucous glands. Mixed glands formed by mucous and serous glands exhibited the same morphological traits of both types of glands. Light microscopic observations revealed that the dorsal and ventral skin showed structural similarities with some minor differences, possibly resulting from their functions.
Keywords: Triturus karelinii; skin structure; cutaneous glands; urodele; PLEURODELES-WALTLII MICH; CUTANEOUS GLANDS; GRANULAR GLANDS; MUCOUS GLANDS; RANA-RIDIBUNDA; AMPHIBIA; ANURA; NEWT; FROG; HISTOCHEMISTRY